EFFECT OF HORMONAL CONTRACEPTIVES ON SERUM ELECTROLYTES AND BLOOD PRESSURE - Haroon, Sadia; Naveed, Abdul Khaliq (Journal of Postgraduate Medical Institute, 2015)
Objective: To find out serum electrolytes and blood pressure in Pakistani females,using oral and injectable contraceptives.Methodology: This descriptive study was conducted at Department of Biochemistryand Molecular Biology, Army Medical College Rawalpindi and variousfamily planning clinics of Rawalpindi and Wah from June 2002 to June2003. Using convenient sampling technique, ninety women were included inthe study. They were divided into three groups: Group A [Oral contraceptiveusers (n=30)]; group B [Injectable users (n=30)], both using contraceptivesfor more than 1 year; and Group C [Controls (n=30)], not using any form ofcontraceptives. Blood pressure was recorded. Fasting blood samples were analyzedfor serum electrolytes. One way anova was used at 95% of confidenceinterval for comparing the data of various groups and p<0.05 was taken assignificant. Pearson's correlation coefficient was calculated between variables.Results: Systolic blood pressure shows a significant difference in both groupsA and B as compared to control (p < 0.05) but diastolic blood pressure washigher in injectable users only (p < 0.05) and group A was higher than groupC but difference was not significant. Serum potassium was less in group Aand B as compared to control but the difference was significant in group B(p<0.01) while in group A was non-significant (p>0.05). Serum sodium showshigher level in group A and B than control but the difference was statisticallynot significantConclusion: In hormonal contraceptive users there are significant changes inblood pressure and electrolytes except serum sodium.